The feasibility of nanofiltration membrane bioreactor (NF-MBR)+reverse osmosis (RO) process for water reclamation: Comparison with ultrafiltration membrane bioreactor (UF-MBR)+RO process - Tay, Ming Feng (2020)
This study examines the feasibility of a novel nanofiltration membrane bioreactor (NF-MBR) followed by reverse osmosis (RO) process for water reclamation at 90% recovery and using an ultrafiltration MBR (UF-MBR)+RO as baseline for comparison. Both MBRs adopted the same external hollow fiber membrane configurations and operating conditions. The collected permeates of the MBRs were subsequently fed to the respective RO systems. The results showed that the NF-MBR (operated at a constant flux of 10 L/m2h) achieved superior MBR permeate quality due to enhanced biodegradation and high rejection capacity of the NF membrane, leading to lower RO fouling rates (∼3.3 times) as compared to the UF-MBR. Further analysis indicated that the cake layer fouling that caused the cake-enhanced osmotic pressure (CEOP) effect contributed predominantly to the transmembrane pressure (TMP) increase in the NF-MBR, while irreversible pore fouling was the major reason for UF membrane fouling. Furthermore, it was found that the biopolymers (i.e., organics with MW > 10 kDa) were the main components present in the foulants of the NF/UF membranes and RO membranes. The analysis indicated that the NF-MBR + RO system at recovery of 90% has comparable energy consumption as the UF-MBR + RO system at recovery of 75%. Our findings proved the feasibility of the NF-MBR + RO for water reclamation at a high recovery rate.